(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2017)
On 8 November 2016, the Government of India announced the demonetization of all 500 and 1,000 banknotes of the Mahatma Gandhi Series. The government claimed that the action would curtail the shadow economy and crack down on the use of illicit and counterfeit cash to fund illegal activity and terrorism. The term Demonetization refers to withdrawal of a particular form of currency from circulation. It is essential whenever there is a change of national currency. The old unit of currency must be removed and substituted with a new currency unit. Demonetization took place for the first time in the year 1946 and second time in 1978. The currency is demonetized for the third th time on 8 Nov. 2016 by our honourable Prime Minister Shri Narender Modi. This is the bold step taken by the govt. for the furtherance of the economy and to put a full stop on black money, laundering and illegal transaction amongst the different nations of the world. The paper discusses the impact of recent demonetization on the Indian system and also the reasons.